Gender-dependent survival benefit from first-line irinotecan in metastatic colorectal cancer. Subgroup analysis of a phase III trial (XELAVIRI-study, AIO-KRK-0110). (April 2021) - Heinrich, Kathrin; Modest, Dominik P.; Ricard, Ingrid; Fischer von Weikersthal, Ludwig; Decker, Thomas; Kaiser, Florian; Graeven, Ullrich; Uhlig, Jens; Schenk, Michael; Freiberg-Richter, Jens; Peuser, Bettina; Denzlinger, Claudio; et al.
Abstract: Background: XELAVIRI compared sequential (Arm A) versus initial (Arm B) irinotecan in combination with fluoropyrimidine plus bevacizumab in patients with metastatic colorectal cancer, trial identification: NCT01249638 . In the full analysis set of the study, non-inferiority of time to failure of strategy (TFS) was not shown. The present analysis was performed to evaluate the effect of gender on treatment outcome and tolerability. Methods: The study end-points overall response rate (ORR), progression-free survival (PFS), TFS and overall survival (OS) were evaluated in female versus male patients and in molecular subgroups (i.e. RAS mutational status). Interaction of treatment and gender was tested by likelihood ratio tests. Results: In total, 281 male and 140 female patients (n = 421) were evaluated. Among the male patients, the ORR was 33.6% without and 58.3% with initial irinotecan (P < 0.001). PFS (hazard ratio [HR] 0.54; 95% confidence interval [CI] 0.42–0.69; P < 0.001) and OS (HR 0.63; 95% CI 0.47–0.85; P = 0.002) were also significantly better with initial irinotecan. Among the female patients, the ORR was 42.7% in Arm A and 43.1% in Arm B, PFS was similar (HR 1.09; 95% CI 0.76–1.55; P = 0.649) without and with initial irinotecan. A strong trend for inferior outcome with regard to OS with initial irinotecan was observed (HR 1.46; 95% CI 0.95–2.24; P = 0.081) and the trend reached significance in the multivariate analysis (HR 1.78; 95% CI 1.08–2.95; P = 0.02). Formal interaction of treatment and gender was observed for ORR (P = 0.018), PFS (P = 0.002) and OS (P = 0.001). Treatment-related adverse events were not significantly different between male and female patients. Conclusions: The present analysis suggests that gender interacts with efficacy of initial irinotecan when used in combination with fluoropyrimidines and bevacizumab. Although male patients derived a significant and clinically meaningful benefit from initial combination chemotherapy, this was not observed in female patients. Highlights: We evaluate the efficacy of initial irinotecan according to gender in mCRC. Male patients seem to benefit from initial irinotecan, whereas women do not. Baseline characteristics and toxicities were similar in male versus female patients.